Development of Small-Medium Industry in Urban Kampong to Realize a Sustainable Creative Economy Area - Siti Sujatini; Euis Puspita D; Dwi Dinariana; Henni Henni; Ari Wijaya (International Journal of Entrepreneurship, Business, and Creative Economy, 2023)
The concept of the creative economy has emerged recently, one of which is the emergence of small and medium industries (IKM) in urban kampong. The creative economy is the driving force for the nation's economy, so its existence needs to be managed and developed. The emergence of the IKM creative economy concept is inseparable from the cultural characteristics of rural communities, which have characteristics of "gotong royong" and "guyub". The community's cultural character triggers the emergence of creative economic areas in urban kampong corridors. This study aims to determine the sustainability of the creative economy area in urban kampong now and in the future by referring to the Penta helix concept. The method used is qualitative, namely conducting observations and interviews and exploring the research that has been carried out regarding the title and the actions needed for the sustainability of the current and future creative economy areas. The location used as a case study is an urban kampong settlement in the Paseban area of Central Jakarta. The results of this study indicate that the sustainability of the creative economy area in urban kampong settlements has not been fully implemented according to the penta helix model, nor has it been implemented sustainably. The researcher's suggestion that the community's creative economy area is always sustainable is that the Penta helix model must always be applied, and cooperation between the 5 elements must always be compact.